2020
DOI: 10.1136/oemed-2020-106745
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for resignation from work after starting infertility treatment among Japanese women: Japan-Female Employment and Mental health in Assisted reproductive technology (J-FEMA) study

Abstract: ObjectiveTo elucidate the risk factors associated with resignation from work of Japanese women undergoing infertility treatment.MethodsA total of 1727 female patients who attended a private fertility clinic in Japan participated in the Japan-Female Employment and Mental health in Assisted reproductive technology study. Questions related to demographic, clinical and socioeconomic characteristics were employed in the questionnaire. Out of the 1727 patients, 1075 patients who were working at the time of initiatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…To recruit eligible samples efficiently, the market research company invited a large sample to the pre-screening, accepted responses in order of arrival and invited randomly selected participants to the survey. However, the sociodemographic distribution of our participants was similar to that of previous clinical settings in Japan [30], and patients with fertility problems tend to have higher education levels. Thus, our data should not be heavily influenced by potential selection bias.…”
Section: Odds Ratios Of "Out-of-pocket Payment"supporting
confidence: 72%
See 2 more Smart Citations
“…To recruit eligible samples efficiently, the market research company invited a large sample to the pre-screening, accepted responses in order of arrival and invited randomly selected participants to the survey. However, the sociodemographic distribution of our participants was similar to that of previous clinical settings in Japan [30], and patients with fertility problems tend to have higher education levels. Thus, our data should not be heavily influenced by potential selection bias.…”
Section: Odds Ratios Of "Out-of-pocket Payment"supporting
confidence: 72%
“…Another important finding of this study relates to women engaged in paid work for 40 h or more per week, who were more likely to choose treatment if they could visit outpatient clinics at night or on weekends. Aligned with rises in parental age and women’s labour force participation [ 2 ], 60% of women receiving fertility care have concerns about missing work [ 29 ], and about 17% of women in Japan resign from their jobs after starting fertility treatment [ 30 ]. We found that medical institutions offering consultation during nights and weekends were preferred by participants working outside the home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear why the Sho pattern in our patient changed 6 months after starting treatment with KBG. Imai et al ( 19 ) reported that lower educational background, longer duration of infertility (>2 years), being non-permanent worker, harassment experience in the workplace, and lack of support within one's company were identified as risk factors for stress after initiating infertility treatment. It is possible that infertility itself and infertility treatment are associated with increased distress.…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 survey found that 7.4% of women who underwent infertility treatment experienced harassment because of it 11) . Of the women who were working at the start of infertility treatment, 16.7-50.1%, or one in 2-6, had left the workforce 10,12,13) , with the lack of workplace support being one of the risk factors for leaving 10,13) . Thus, women are subjected to various occupational stressors owing to pregnancy and childbirth.…”
Section: Introductionmentioning
confidence: 99%